2023
DOI: 10.3390/s23146318
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction Behaviors Identification of Construction Workers Based on ST-GCN and YOLO

Abstract: The construction industry is accident-prone, and unsafe behaviors of construction workers have been identified as a leading cause of accidents. One important countermeasure to prevent accidents is monitoring and managing those unsafe behaviors. The most popular way of detecting and identifying workers’ unsafe behaviors is the computer vision-based intelligent monitoring system. However, most of the existing research or products focused only on the workers’ behaviors (i.e., motions) recognition, limited studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Table 1 presents other papers that integrated multiple algorithms to achieve improved visual recognition. [113] Detect workers and predict their movement trajectories SURF + improved GMM + HOG + SVM Li et al [114] Hardhat-wearing tracking detection YOLO v5 + Strong SORT Lee et al [115] PPE usage detection YOLACT employs MobineNetv3 + DeepSORT Li et al [116] Recognize construction workers' activities YOLO + ST-GCN (Spatial temporal graph convolutional networks)…”
Section: B Computer Vision Algorithms' Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents other papers that integrated multiple algorithms to achieve improved visual recognition. [113] Detect workers and predict their movement trajectories SURF + improved GMM + HOG + SVM Li et al [114] Hardhat-wearing tracking detection YOLO v5 + Strong SORT Lee et al [115] PPE usage detection YOLACT employs MobineNetv3 + DeepSORT Li et al [116] Recognize construction workers' activities YOLO + ST-GCN (Spatial temporal graph convolutional networks)…”
Section: B Computer Vision Algorithms' Innovationmentioning
confidence: 99%
“…Similarly, Cai et al [128] introduced an attention direction estimation method to identify groups of construction workers and subsequently classified their activities using LSTM. Li et al [116] identified three activities of construction workers through YOLO and ST-GCN, which are throwing, operating and crossing. Torabi et al [129] and Yang et al [96] employed YOWO53 and Transformer, respectively, demonstrating high recognition accuracy on today's advanced computing hardware.…”
Section: B Recognition Of Workers' Construction Activitiesmentioning
confidence: 99%
“…This method was then used for activity classification through LSTM. Li et al [60] identified three types of construction worker behaviors: throwing, operating, and crossing, using YOLO and ST-GCN. Torabi et al [61] proposed a YOWO53 model that recognizes construction activities.…”
Section: Computer Vision Application In Workers' Construction Activit...mentioning
confidence: 99%
“…The use of intelligent monitoring systems based on computer vision in the field of security is one of the most popular methods today [24]. In the study [25], the authors developed methods for detecting safety violations among workers. As a result, a decision-making algorithm was defined that takes into account the interaction between the human, machine and material.…”
Section: Introductionmentioning
confidence: 99%